2016
DOI: 10.1007/s12265-016-9713-1
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 and Risk of Arrhythmias, Heart Failure, or Death in Patients with Mildly Symptomatic Heart Failure: Results from MADIT-CRT

Abstract: Soluble ST2 is an established biomarker of heart failure (HF) progression. Data about its prognostic implications in patients with mildly symptomatic HF eligible to receive cardiac resynchronization therapy defibrillators (CRT-D) are limited. In a cohort of 684 patients enrolled in Multicenter Automated Defibrillator Implantation Trial (MADIT)-CRT, levels of soluble ST2 (sST2) were serially assessed at baseline and 1 year (n = 410). In multivariable-adjusted models, elevated baseline sST2 was associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
0
24
0
3
Order By: Relevance
“…An expected result of such changes was a statistically significant increase of the "soluble" ST2 receptor (sST2) in the plasma of the rats with experimental myocardial infarction. It is known that the receptor ST2 (suppression of tumorigenicity-2) is a representative of the interleukin IL-1 receptors family [12][13][14]. ST2 exists in two isoforms: transmembrane (ST2L) and "soluble" (sST2), which is not bound to the cell or membrane and circulates freely in the circulatory system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An expected result of such changes was a statistically significant increase of the "soluble" ST2 receptor (sST2) in the plasma of the rats with experimental myocardial infarction. It is known that the receptor ST2 (suppression of tumorigenicity-2) is a representative of the interleukin IL-1 receptors family [12][13][14]. ST2 exists in two isoforms: transmembrane (ST2L) and "soluble" (sST2), which is not bound to the cell or membrane and circulates freely in the circulatory system.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have shown that interleukin-33 (IL-33) is the ligand of the ST2 receptor [12]. Hypoxic damage to cardiomyocytes and fibroblasts, excessive pressure and stretching are the main momentum of the IL-33/ST2 system activation in the heart [14]. IL-33 performs its cardioprotective effect in the interaction with the ST2L receptor [13][14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in patients with mildly symptomatic HF evaluated during the MADIT-CRT trial, a 10% elevation of sST2 levels alone over one year, was shown to be predictive of increased risk of onset of ventricular arrhythmias and death. Nevertheless, in the same study it was shown, that an elevated sST2 baseline is not directly predictive of ventricular arrhythmias [90].…”
Section: Soluble St2 (Sst2)mentioning
confidence: 90%
“…Despite those facts, it is recommended to start the assessment in clinical practice with cTnT and evaluate cardiac troponin I (cTnI) in those who present increased concentrations of cTnT [14]. sST2 is associated with increased risk of death, heart failure or ventricular arrhythmia, as it reduces protective impact of IL-33 on myocardium [6,17]. Yet, in our study, no correlations were found between IL-33, sST2 and clinical symptoms indicating cardiovascular involvement or biochemical markers of cardiac injury such as CK-MB, troponin T, troponin I or NT-proBNP.…”
Section: Discussionmentioning
confidence: 99%